The Role of Ulama and Muslim Networks in Countering Radicalism - Siddiq, Akhmad; Imama, Lely Shofa (FITK UIN Walisongo, 2024)
The accumulation of religious temperament can affect human interaction. In the context of religious behavior, Islam addresses two terms known as al-ifrāṭ (excess) and al-tafrīṭ (neglect). The first refers to the exorbitance of the individual in experiencing and expressing his religiosity, while the second means ignoring a certain religious order easily. Both are conflictual. In terms of inter-religious interaction, believers' excessive religiosity could neglect others' religiosity. In this regard, some people tend to avoid the presence of others due to their excessive religious confession. This research explores religious networks conducted by Muslim organizations in Pamekasan, Madura, that could bridge inter-religious relations between Muslims and others, especially between Muslims and Christians. Through observation and in-depth interviews, this research describes the so-called religious excessiveness that could lead religious believers to respect different religions and faiths. The paper found that the ulama network could become an effective medium to reduce religious excessiveness and promote religious moderation.